Instrumen Penilaian Nyeri pada Anak dengan Gangguan Kognitif: A Literatute Review - Dhina Widayati (Journal of Bionursing, 2021)
Introduction: Difficulty in assessing pain in someone who cannot express the pain they feel, for example in children with cognitive impairment, provides a significant obstacle in pain management. The purpose of this study is to review the literature containing pain assessment instruments in children with cognitive impairment and to discuss instruments that can be applied effectively and have clinical use. Method: Search for English articles in the Medline, Cinahl, and PubMed databases, and is limited from 1990 to 2013. Through keywords according to topic and obtained 5 articles that were reviewed. Result : Pain assessment in children with cognitive impairment can be done through rFLACC, NCCPC-PV, NCCPC-R and NAPI. rFLACC is the most effective instrument and has great clinical utility with ICC : 0.73-0.9). Analysis: rFLACC assesses 5 indicators (face expression, leg, activity, cry & consoability) that are simpler and easier to apply to all children with cognitive impairment at all levels. Discussion: Elective postoperative pain assessment in clinical settings in children with cognitive impairment can be performed with rFLACC. In an effort to increase the reliability of the instrument, the improvement of leg items and activities can be the basis for further research.